ICE-COLD SALINE DAN EPINEPHRINE DALAM TATALAKSANA PERDARAHAN PADA TINDAKAN BRONKOSKOPI - kornelis aribowo (Universitas Fort De Kock, 2022)
This case report describes the management of bleeding that occurs from sampling during bronchoscopy. There are many measures to treat bleeding during sampling, namely bronchoscopy suction, iced-cold saline, vasoactive drugs, bronchoscopy tamponade, balloon tamponade, fibrin glue, bronchial tree isolation, laser coagulation, electrocautery. The choice of ice-cold saline and epinephrine in a 57-year-old male patient with lung malignancy and a cryobiopsy on bronchoscopy was the main choice in treating bleeding during the procedure.